PENGARUH PEMBANGUNAN INFRASTRUKTUR FISIK DALAM PENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA MALINTUT KECAMATAN RAREN BATUAH KABUPATEN BARITO TIMUR - Sugianoor Sugianoor (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2020)
The purpose of this study was to determine the Effect of Physical Infrastructure Development in Improving Community Welfare Malintut Village, Raren Batuah District, East Barito Regency. This research was conducted with a quantitative approach which is a research approach that uses the calculation of numbers which are then analyzed by statisticsthat physical development affects the socio-economic improvement of the community.